Abnormal psychology - Davison, Gerald C.; Kring, Ann M. (Wiley, 2004)
"With Davison, Neale & Kring's Ninth Edition of Abnormal Psychology, you have the opportunity to explore the many points of view and the latest theories and research in our ever-changing search for answers to the complex questions of psychopathology."--Boof Jacket.